LINGUISTICS AND TRANSLATION METHODS: A PERSPECTIVE THROUGH UZBEK LITERATURE - Abdulaziz Abdullayev; Aziza Atoboyeva (Western European Studies, 2025)
This paper explores the relationship between linguistics and translation methods with a focus on Uzbek literature. It examines how linguistic principles — including semantics, pragmatics, and cultural linguistics — shape the process of translating literary works. By analyzing selected texts by Abdulla Qodiriy, Cho‘lpon, and O‘tkiir Hoshimov, the study highlights the role of cultural context, idiomatic expression, and stylistic nuance in successful translation. The research concludes that effective literary[1] translation requires a balance between linguistic accuracy and cultural adaptation to preserve the original author’s intent and national identity
Keywords: linguistics; translation methods; Uzbek literature